Peran Kepuasan Kerja Dalam Memediasi Hubungan Antara Dukungan Rekan Kerja dan Work Life Balance Terhadap Kinerja Pegawai - Nurdin Yusuf; Olfin Ishak; Firman Dera; Mohammad Rolli Paramata (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This study aims to analyze the influence of coworker support and work-life balance on employee performance, with job satisfaction serving as a mediating variable at the Regional Drinking Water Company (PDAM) Tirta Limutu. The primary focus of this research is to examine how social support from colleagues and employees’ ability to maintain a balance between professional and personal life contribute to improved job performance, both directly and indirectly through enhanced job satisfaction. A quantitative approach was employed using path analysis as the analytical technique. Data were collected through questionnaires distributed to 94 employees of PDAM Tirta Limutu, who served as the research respondents. The data were analyzed using LISREL 8.70 to test the causal relationships among the variables. The results indicate that coworker support and work-life balance have a positive and significant effect on job satisfaction. Furthermore, job satisfaction also exerts a positive and significant influence on employee performance. The findings confirm that job satisfaction functions as a partial mediator, meaning that both coworker support and work-life balance influence employee performance directly and indirectly through job satisfaction. Practically, this study highlights the importance of fostering a supportive organizational culture and implementing policies that promote work-life balance to achieve sustainable employee performance.